HPAI impacts on Chinese chicken meat supply and demand. Issue 3 (1st September 2017) - Huang, Z.; Loch, A.; Findlay, C.; Wang, J.
Abstract : Chicken meat is an economically important part of Chinese food security, but has suffered relatively consistent highly pathogenic avian influenza (HPAI) outbreaks since 2004. This review evaluates the extent of quantity losses caused by HPAI events on Chinese chicken meat supply and demand (domestic production, consumption, imports and exports) between 2004 and 2013, using a partial equilibrium model. The largest losses were experienced in 2004 and 2005 (4, 496, 700 tons) which accounted for 38.84% and 33.76% of total respectively. Across the full review period the largest impacts were on per capita consumption (2.7 million tons) followed by production (2.5 million tons), imports (0.73 million tons) and exports (0.21 million tons). Research suggests that higher imports of chicken meat during HPAI events, branding strategies and investment in food safety management through the sector may help to avoid or minimise future HPAI losses in China.